2010
DOI: 10.4049/jimmunol.1000095
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TLR4-Induced IκB Kinase Activity by the RON Receptor Tyrosine Kinase and Its Ligand, Macrophage-Stimulating Protein

Abstract: The RON receptor tyrosine kinase regulates the balance between classical (M1) and alternative (M2) macrophage activation. In primary macrophages, the ligand for Ron, macrophage-stimulating protein (MSP), inhibits the expression of inducible NO synthase, a marker of classically activated macrophages, whereas promoting the expression of arginase I, a marker of alternative activation. Ron−/− mice express increased levels of IL-12, a product of classically activated macrophages, after endotoxin administration, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 40 publications
5
39
0
Order By: Relevance
“…The degree of inflammation at these sites correlates with the ratio of M1/M2 macrophages as broadly defined, and an imbalance of these populations results in disease progression (34)(35)(36). We have previously shown that Ron regulates the balance of inflammatory versus reparative macrophages both in vitro and in vivo (14)(15)(16). In order to determine whether Ron plays a role in the progression of obesity-associated disease, we placed 6-wk-old male mice on an HFD for up to 18 wk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of inflammation at these sites correlates with the ratio of M1/M2 macrophages as broadly defined, and an imbalance of these populations results in disease progression (34)(35)(36). We have previously shown that Ron regulates the balance of inflammatory versus reparative macrophages both in vitro and in vivo (14)(15)(16). In order to determine whether Ron plays a role in the progression of obesity-associated disease, we placed 6-wk-old male mice on an HFD for up to 18 wk.…”
Section: Resultsmentioning
confidence: 99%
“…NF-kB and Stat1 promote an inflammatory phenotype in macrophages by coordinately inducing inflammatory gene expression. Ron inhibits the activation of NF-kB in response to LPS by targeting the ubiquitination of TNFR-associated factor 6 and the nuclear localization of NF-kB (16,18,19). Ron also inhibits IFN-g-induced Stat1 phosphorylation, associated with the upregulation of the inhibitors of cytokine signaling, suppressor of cytokine signaling 1 and 3 (12,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,26 In macrophages, activation of RON by MSP results in attenuation of immune responses. 2933 Previously, we and others have shown that host RON signaling negatively regulates antitumor immunity in mouse models of cancer. 31,34,35 Importantly, host RON was critical for conversion of micrometastatic lesions into overt clinical metastases, a step that is thought to be rate-limiting in the deadly metastatic cascade.…”
Section: Introductionmentioning
confidence: 99%
“…MST1R encodes a cell surface receptor for macrophage-stimulating 1 (MST1, also known as MSP) with tyrosine kinase activity. Previous studies show that MST1R plays a critical function in host defense: (i) It is predominantly expressed in the tissue-resident macrophages, which promote tissue repair and inhibit inflammation by repressing the production of proinflammatory molecules induced by pathogens (14)(15)(16)(17) and (ii) MST1R expression is detected in the ciliated epithelial cells in the normal nasal mucosa, and activation of MST1R signaling can increase the ciliary motility to prevent chronic infection (18). Previous studies and our WES data strongly support the role of MST1R as an NPC susceptibility gene.…”
Section: Significancementioning
confidence: 99%